Funny girl : a novel - Hornby, Nick (Riverhead Books, a member of Penguin Group (USA), 2015)
"From the bestselling author of High Fidelity, About a Boy, and A Long Way Down comes a highly anticipated new novel. Set in 1960's London, Funny Girl is a lively account of the adventures of the intrepid young Sophie Straw as she navigates her transformation from provincial ingenue to television starlet amid a constellation of delightful characters. Insightful and humorous, Nick Hornby's latest does what he does best: endears us to a cast of characters who are funny if flawed, and forces us to examine ourselves in the process. "--